Assegai - Smith, Wilbur A (New York Thomas Dunne Books/St. Martin's Press, 2009)
On the eve of the World War I, ex-soldier turned professional hunter Leon Courtney is recruited by his uncle Penrod Ballantyne, commander of the British forces in East Africa, to gather information on one of his clients, Count Otto von Meerbach, and soon finds himself left alone to frustrate von Meerbach's plan to wipe out the British forces in Africa
Map on endpapers
1
Keywords: British -- Africa, East -- Fiction; Germans -- Africa, East -- Fiction; Hunting guides -- Fiction; Safaris -- Africa, East -- Fiction; Historical fiction; Spy stories